Functional Outcomes of Revision Osteosynthesis after Failure of Surgical Treatment of Patellar Fractures - Müller, Elena Caroline; Frosch, Karl-Heinz (The Journal of Knee Surgery, 2019)
Patellar fractures account for approximately 1% of all skeletal fractures. These fractures are rare; however, because of the crucial function of the patella in the extensor mechanism of the knee, they may lead to serious impairment. New data are revealing functional impairment remains common even with improved surgical techniques. The aim of this study was to assess the functional outcomes of patients after revision surgery in cases of secondary fracture dislocation or persistent articular incongruity. This study included 16 patients with a mean age of 51.8 years (range: 16–85 years) with a mean follow-up of 35.1 months. According to the AO/OTA classification, 15 patients had a C-type fracture, including 10 patients with C3 fracture. Thirteen patients were initially treated with tension band wiring via K-wires or cannulated screws. Revision surgery was performed because of persistent articular incongruity in five patients and secondary fracture dislocation or refracture in 11 patients. We analyzed pain (visual analog scale [0–10]), satisfaction, range of motion (ROM), Böstman's score, Lysholm's score, and knee injury and osteoarthritis outcome score (KOOS) after revision surgery and could extract follow-up data from 15 patients. Mean pain score at rest was 0.57 (range: 0–3.5) and on exertion 2.79 (range: 0–8). The measurement of the ROM of the affected knee compared with that of the opposite knee revealed complete extension. Mean flexion was 123 degrees, in the corresponding knee it was 136 degrees (p = 0.05). The mean postoperative Böstman's and Lysholm's scores were 25.11 (good, maximum: 30) and 78.67 (moderate, maximum: 100), respectively. KOOS was as follows: symptoms, 66.8 points; pain, 77.55 points; activity of daily living (ADL), 75.67 points; and quality of life, 56.25 points. The results of this study suggested that early revision surgery after failure of primary osteosynthesis with secondary anatomic reconstruction and good radiological results leads to satisfactory functional outcomes with persistent functional deficits.
Keywords: patellar fracture; revision surgery; functional outcome